2016
DOI: 10.14725/gjanp.v3n1.a1109
|View full text |Cite
|
Sign up to set email alerts
|

住院老年人误吸风险及对误吸认知的调查分析

Abstract: Objective: To investigate the aspiration risk and the aspiration cognition of elderly inpatients. Method: A self-designed questionnaire about the aspiration risk and the aspiration cognition was applied to survey the hospitalized elderly. Result: The aspiration risk of the elderly was higher, up to 41.3%, characterized by coming up with various symptoms. The illnesses the elderly suffering from, types of medication, motion ability and the state of consciousness were the risk factors resulting in aspiration (P<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…These results are consistent with previous study findings, which indicate that 85.09% and 86.4% of patients are satisfied or very satisfied with the doctor services and nurse care, respectively. 30 Research by Kippenbrock and colleagues 31 has also confirmed this result. This study extended the research that has not only surveyed women's satisfaction with healthcare providers but has also explored the relationship between women's satisfaction with healthcare providers and breast cancer screening practices.…”
Section: Discussionmentioning
confidence: 76%
“…These results are consistent with previous study findings, which indicate that 85.09% and 86.4% of patients are satisfied or very satisfied with the doctor services and nurse care, respectively. 30 Research by Kippenbrock and colleagues 31 has also confirmed this result. This study extended the research that has not only surveyed women's satisfaction with healthcare providers but has also explored the relationship between women's satisfaction with healthcare providers and breast cancer screening practices.…”
Section: Discussionmentioning
confidence: 76%